An Evaluation of Supramaximally Loaded Eccentric Leg Press Exercise. Issue 10 (October 2018) - Harden, Mellissa; Wolf, Alex; Russell, Mark; Hicks, Kirsty M.; French, Duncan; Howatson, Glyn
Abstract : Abstract: Harden, M, Wolf, A, Russell, M, Hicks, KM, French, D, and Howatson, G. An evaluation of supramaximally loaded eccentric leg press exercise. J Strength Cond Res 32(10): 2708–2714, 2018—High-intensity eccentric exercise is a potent stimulus for neuromuscular adaptation. A greater understanding of the mechanical stimuli afforded by this exercise will aid the prescription of future eccentric training regimens. This study sought to investigate the mechanical characteristics of supramaximally loaded eccentric exercise when using a custom-built leg press machine. Using a within-subject, repeated-measures design, 15 strength trained subjects (age, 31 ± 7 years; height, 180.0 ± 6.8 cm; body mass, 81.5 ± 13.9 kg) were assessed under 3 different conditions: low (LO), moderate (MOD), and high (HI) intensity, which were equivalent in intensity to 110, 130, and 150%, respectively, of peak force during an isometric maximal voluntary contraction (IMVC) performed on leg press at 90° knee flexion. All loading conditions demonstrated a similar pattern of mechanical profile; however, the variables underpinning each profile showed significant ( p < 0.01) load-dependent response (LO vs. MOD, MOD vs. HI, LO vs. HI) for all variables, except for average acceleration. Average force associated with each loading conditions exceeded IMVC but equated to a lower intensity than what was prescribed. Repetitions under higher relative load intensity stimulated greater average force output, faster descent velocity, greater magnitude of acceleration, shorter time under tension, and a decline in force output at the end range of motion. This research provides new data regarding the fundamental mechanical characteristics underpinning supramaximally loaded eccentric leg press exercise. The information gathered in the study provides a foundation for practitioners to consider when devising loading strategies and implementing or evaluating supramaximally loaded eccentric exercise when using a similar exercise and device.